PROGRESS STUDY: Progression of chronic kidney disease in children and heat shock proteins - ALPAY, HARİKA; GÖKCE, İBRAHİM; YILDIZ, NURDAN (SPRINGER, 2021)
Various molecular and cellular processes are involved in renal fibrosis, such as oxidative stress, inflammation, endothelial cell injury, and apoptosis. Heat shock proteins (HSPs) are implicated in the progression of chronic kidney disease (CKD). Our aim was to evaluate changes in urine and serum HSP levels over time and their relationships with the clinical parameters of CKD in children. In total, 117 children with CKD and 56 healthy children were examined. The CKD group was followed up prospectively for 24 months. Serum and urine HSP27, HSP40, HSP47, HSP60, HSP70, HSP72, and HSP90 levels and serum anti-HSP60 and anti-HSP70 levels were measured by ELISA at baseline, 12 months, and 24 months. The urine levels of all HSPs and the serum levels of HSP40, HSP47, HSP60, HSP70, anti-HSP60, and anti-HSP70 were higher at baseline in the CKD group than in the control group. Over the months, serum HSP47 and HSP60 levels steadily decreased, whereas HSP90 and anti-HSP60 levels steadily increased. Urine HSP levels were elevated in children with CKD; however, with the exception of HSP90, they decreased over time. In conclusion, our study demonstrates that CKD progression is a complicated process that involves HSPs, but they do not predict CKD progression. The protective role of HSPs against CKD may weaken over time, and HSP90 may have a detrimental effect on the disease course.
Keywords: Chronic kidney disease; CKD; Heat shock protein; HSP; Progression; HSP70; EXPRESSION; CELLS; DEGRADATION; CHAPERONES; APOPTOSIS; FIBROSIS; MARKER; DAMAGE; HSP47